Тhe Importance of Learning A Foreign Language in the System of Training Highly Qualified Personnel in the Field of Transport (Texas Journal of Multidisciplinary Studies, 2022)
This article provides examples from practice the author's work when teaching a foreign language in the classroom, justifies the effectiveness of using various methods in the process studying a foreign language at a technical university, the article is devoted to the effective use of information and communication tools.